2020
DOI: 10.21323/2414-438x-2020-5-2-20-25
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histological indicators of blood and m. longissimus dorsi of young bulls of Kazakh white-headed breed of different genotypes by the CAPN1 and GH genes

Abstract: The use of molecular genetic markers for productivity is one of the modern approaches in breeding beef cattle. The article presents the results of the studies on the influence of genotypes by the calpain (CAPN1) and growth hormone (GH) genes on live weight, fatty acid composition of blood plasma, quantitative and qualitative indicators of meat of young cattle of Kazakh white-headed breed. It was established that animals of the homozygous geno-types СС–CAPN1 and VV-GH had a larger live weight and its average da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The effect of the BB genotype (TT in this study) on the minimum feed intake of young animals was confirmed in the study by Siadkowska et al [37] on Holstein-Friesian cattle. A negative effect of the allele Selionova and Plakhtyukova [41] found the effect of amino acid substitution Leu → Val at codon 127 of the GH gene on the variability of the LW and ADG when studying the differences in weight growth of Kazakh white-headed bulls. In this case, young animals with the VV genotype (GG in our case) had a significant (p < 0.05-0.01) advantage in body weight at weaning and 1 year of age, as well as in the growth rate during the control rearing period.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the BB genotype (TT in this study) on the minimum feed intake of young animals was confirmed in the study by Siadkowska et al [37] on Holstein-Friesian cattle. A negative effect of the allele Selionova and Plakhtyukova [41] found the effect of amino acid substitution Leu → Val at codon 127 of the GH gene on the variability of the LW and ADG when studying the differences in weight growth of Kazakh white-headed bulls. In this case, young animals with the VV genotype (GG in our case) had a significant (p < 0.05-0.01) advantage in body weight at weaning and 1 year of age, as well as in the growth rate during the control rearing period.…”
Section: Discussionmentioning
confidence: 99%